Urban Management Strategies Based on Smart Governance and Big Data Analytics to Improve the Efficiency of Urban Public Services - Irawan, Bambang (ADMAN: Journal of Contemporary Administration and Management, 2025)
This study aims to explore in depth how urban management strategies that integrate smart governance and big data analytics can improve the efficiency of public services in urban environments. Using a descriptive qualitative approach and a literature review method, this research analyzes 24 rigorously selected scholarly articles from a total of 50 publications spanning from 1989 to 2025, sourced from Google Scholar and other credible online databases. The findings indicate that smart governance—characterized by collaboration, transparency, and participation—can be enhanced by the analytical capabilities of big data in identifying citizen needs, accelerating decision-making, and optimizing resource allocation. Case studies from cities such as Amsterdam, Surabaya, and Dublin demonstrate that the integration of technology and managerial strategies can expedite service response times, reduce operational costs, and increase public satisfaction. Nevertheless, the success of this strategy relies heavily on the readiness of digital infrastructure, the data literacy of public officials, and the establishment of standardized data governance frameworks. This study provides both theoretical and practical contributions to the development of adaptive, efficient, and inclusive technology-based urban governance models.